PELATIHAN UMKM DESA REJOSARI MENJADI GO DIGITAL MELALUI DIGITAL MARKETING DAN PENGELOLAAN KEUANGAN DIGITAL - Fatichatur Rachmaniyah; Anisa Ulfah; Intan Sari Finas; Alif Indah Maulida (P3M Politeknik Negeri Malang, 2024)
In the digital era, MSMEs are faced with the challenge of adapting to technology in order to remain competitive. This study aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) of herbal drinks in Rejosari Village, Lamongan. This is done through digital marketing and financial management training using the Qasir application. This training includes socialization of the importance of digital marketing and direct practice using social media platforms and financial management applications. The results of the study showed a significant increase in participants' digital knowledge and skills. In addition, participants showed a high interest in applying the knowledge gained in running their businesses. However, there are still several obstacles faced, such as the lack of digital literacy. This study concludes that digital training can be an effective solution to improve the competitiveness of MSMEs in rural areas.